Paraplegia - Juan Antonio Ibarra Arias, José; Alberto Cuellar Ramos, Carlos (IntechOpen, 2021)
In the last decade, diverse research areas have developed novel approaches to overcome dysfunctions after a spinal cord injury (SCI). Even though motor restoration attracts the most clinical attention, sensory, autonomic, and mental health are also aspects fundamental to improving the quality of life of SCI patients. Over four sections of therapeutic, rehabilitation, and technological approaches, this book examines preclinical and clinical studies using mesenchymal stem cells and pharmacological or electrical stimulation strategies. Chapters also address the impact of paraplegia and associated loss of autonomic functions, including bowel and sexual dysfunction, as well as the convergence of new technologies aimed at providing postural support and enhancing mobility.